Enhancing crop genepool use: capturing wild relative and landrace diversity for crop improvement - Maxted, Nigel; Dulloo, Mohammad Ehsan; Ford-Lloyd, B.V. (CAB International, 2016)
Maintaining food security in the face of human population increase and climate change is one of the critical challenges facing us in the 21st Century. Utilisation of the full range of agrobiodiversity will be a necessary tool in addressing this challenge. In this book a team of international contributors review all aspects of utilization and conservation of crop wild relative (CWR) and landrace (LR) diversity as a basis for crop improvement and future food security.